What is the story of Batman? - Burgan, Michael (What is the story of?, 2020)
"Bruce Wayne, a wealthy American philanthropist and business owner, and Batman, his crime-fighting alter ego, have been entertaining audiences since 1939. The character was so popular after appearing in Detective Comics that DC Comics decided to give Batman a comic book of his own. In doing so, they created one of the company's most successful franchises. Author Michael Burgan details the history of Batman--from his tragic origin story and his infamous arch enemies--to his iconic depictions in television and movies throughout the years. This book shows readers why this superhero with no superpowers is so beloved around the world"--